Nice and mean - Leader, Jessica (New York : Aladdin M!X, 2010)
When Marina and Sachi, two girls at opposite ends of the niceness scale, are forced to work together on the big semester project for their video class, but each has her own ideas about the project's objective.
Keywords: Interpersonal relations -- Fiction; Friendship -- Fiction; Video recordings -- Production and direction -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Video recordings -- Production and direction -- Juvenile fiction